KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI SELF EFFICACY SISWA DAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DI SMP NEGERI 20 PALEMBANG - Destiniar Destiniar; Jumroh Jumroh; Devi Maya Sari (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2019)
This research is aimed to know the influence of Think Pair Share (TPS) learning model on students' mathematical concept comprehension in terms of self efficacy of SMP Negeri 20 Palembang students. The method used is the experimental method with a population of 316 students and samples taken as many as 63 students. One experimental class of 32 students who received treatment model Think Pair Share (TPS) and one control class were 31 students who received conventional learning treatment. Data were analyzed by using two-way ANOVA. Based on the analysis of research results indicate that there is influence of learning model of Think Pair Share (TPS) to students' mathematical concept, there is influence of concept comprehension ability in terms of student self efficacy, and there is no interaction between Think Pair Share (TPS) and self efficacy to the ability of understanding mathematical concepts of students of class VII SMP Negeri 20 Palembang. Keywords: Ability to Understand Mathematical Concepts, Self Efficacy, Think Pair Share